The Influence of Hard Skills and Soft Skills on the Performance of Bengkulu City Education Office Employees - Pratama, Meylan; Nasution, Suswati; Nurzam, Nurzam (Universitas Dehasen Bengkulu, 2022)
The purpose of this study is to determine the effect of hard skills and soft skills on employee performance at Education Department of Bengkulu City. This research is a quantitative research. The method used in this study is a questionnaire method, with a sample of 102 employees who have become ASN employees at Education Department of Bengkulu City. The results show that multiple linear regression Y = 19.309 + 0.295 (X1) + 0.360 (X2) + 1.053, meaning that the hard skills (X1) and soft skills (X2) variables have a positive or unidirectional relationship to employee performance (Y) at Education Department of Bengkulu City. The results of the t-test that the hard skill variable (X1) shows t count 3.779>t table 1.984 and a significance of 0.000<0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that hard skills (X1) have a positive and significant effect on employee performance (Y) at Education Department of Bengkulu City, then the results of the soft skills variable t test (X2) showed t count value of 8.231>t table 1.984 and a significance of 0.000 <0.05, then the results of the hypothesis Ha were accepted and Ho was rejected, meaning that soft skills (X2) had a positive effect and significantly to the performance of employees (Y) at Education Department of Bengkulu City. The result of the F count test is greater than F table, which is 33,939>2,46, it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between hard skills (X1) and soft skills (X2) on employee performance (Y) at Education Department of Bengkulu City. This can be seen at a significance level of 0.000<0.05.